Genetic Characterization of AmpC and Extended-Spectrum Beta-Lactamase Phenotypes in Escherichia coli and Salmonella From Alberta Broiler Chickens - Tran, Tam; Checkley, Sylvia; Caffrey, Niamh; Mainali, Chunu; Gow, Sheryl; Agunos, Agnes; Liljebjelke, Karen (Frontiers in Cellular and Infection Microbiology, 2021)
Horizontal gene transfer is an important mechanism which facilitates bacterial populations in overcoming antimicrobial treatment. In this study, a total of 120 Escherichia coli and 62 Salmonella enterica subsp. enterica isolates were isolated from broiler chicken farms in Alberta. Fourteen serovars were identified among Salmonella isolates. Thirty one percent of E. coli isolates (37/120) were multiclass drug resistant (resistant to ≥ 3 drug classes), while only about 16% of Salmonella isolates (10/62) were multiclass drug resistant. Among those, eight E. coli isolates had an AmpC-type phenotype, and one Salmonella isolate had an extended-spectrum beta-lactamase (ESBL)-type β-lactamase phenotype. We identified both AmpC-type (blaCMY-2) and ESBL-type (blaTEM) genes in both E. coli and Salmonella isolates. Plasmids from eight of nine E. coli and Salmonella isolates were transferred to recipient strain E. coli J53 through conjugation. Transferable plasmids in the eight E. coli and Salmonella isolates were also transferred into a lab-made sodium azide-resistant Salmonella recipient through conjugation. The class 1 integrase gene, int1, was detected on plasmids from two E. coli isolates. Further investigation of class 1 integron cassette regions revealed the presence of an aadA gene encoding streptomycin 3''-adenylyltransferase, an aadA1a/aadA2 gene encoding aminoglycoside 3''-O-adenyltransferase, and a putative adenylyltransferase gene. This study provides some insight into potential horizontal gene transfer events of antimicrobial resistance genes between E. coli and Salmonella in broiler chicken production.